Efek Ekstrak Air Biji Pepaya (Carica papaya L.) terhadap Fertilitas Mencit (Mus musculus L.) Betina - Muhammad Feraldi Firdaus; Agung Janika Sitasiwi; Siti Muflichatun Mardiati (Jurnal Sain Veteriner, 2017)
Papaya seeds were known as medicinal plant which have anti-fertility potencies. So it could be used as a herbal contraceptive. The purpose of this study was to test the anti-fertility effect of Papaya seed water extract on mice (Mus musculus L.) fertility which proved by pregnancy rate, litters number and sex ratio of litters. This study was designed by Completely Randomized Design, using 15 female Swiss Webster mice that were divided into 5 treatment groups with triplicates. The K(-) group were treated by distilled water; K(+) group were treated by contraceptive pills; P1, P2, P3 groups that were treated by papaya seeds extract with 1.4, 3.5 and 7 mg/animal/day respectively. Each treatment was given orally with 0.5 ml in volume for 21 days. At the end of treatment, mice was mated. The observed parameters were pregnancies occurence, litters number and sex ratio of the litters. The litters number data were analyzed by Analysis of Variance. The results showed there was differences in pregnancy time and sex ratio between control and treatment groups, but there was not significantly different in litters number. It could be concluded that the fertility of mice was inihibited by water extract of papaya seeds.